Situation #219: Fleeting Media. Publishing Post-Photography - Stylianou-Lambert, Theopisti (My University, 2026)
“Situation #219: Fleeting Media. Publishing Post-Photography”, Passage of Fotobibliothek, Switzerland. Curated by Mona Schubert. (with “Tracking the Loving Gaze”)